Implementasi One Time Password (OTP) Menggunakan Fungsi Hash Algoritma SHA-512 Pada Aplikasi Penagihan Hutang PT. XHT - Rizki, Rizki; Mulyati, Sri (Jurnal Pendidikan Informatika (EDUMATIC), 2020)
PT. XHT is a private company engaged in debt collection. This company has a web-based debt collection system. However, there has been a theft of usernames and passwords on the running system. This is due to many things, including passwords that are too easy. One solution to overcome this is to increase authentication security, which is a One-Time Password system. In this research, login security system is created using the SHA-512 hash function. In build this system using the Waterfall method as the life cycle of software development (SDLC). This system is a random code can only be used once. The test involved several parties, including Media Expert and Material Expert, and using the black box method. Black box test results indicate the feasibility of the function from the input and output buttons. Meanwhile, the results from the test by the Media Expert scored 82%, while the Material Expert was 75%. So it can be concluded that the One-Time Password login system using SHA-512 is suitable for user security.